Human Cystic Echinococcosis in Different Geographical Zones of Iran: An Observational Study during 1995-2014 - Mohammad ZEINALI; Mehdi MOHEBALI; Mohammad Reza SHIRZADI; Bahman RAHIMI ESBOEI; Hossain ERFANI; Jamshid POURMOZAFARI; Mahboube GHANBARI (Tehran University of Medical Sciences, 2017)
Background: Cystic Echinococcosis (CE) is a serious zoonotic parasitic disease in Iran. This study aimed to show the trend of the confirmed disease from 1995 to 2014 and to describe some of epidemiological aspects of the disease in Iran. Methods: This retrospective study has been designed based on data collected from 8518 cases of CE among various geographical locations of Iran. Results: The average annual number of human cases of CE was 274.8. Among 31 provinces of Iran, Razavi Khorasan from northeast part of Iran was the highest human CE infected province with the 1801 cases and Hormozgan Province in south part of the country showed the lowest the disease with the only one case of CE in 2009. Liver and lungs with the infection rate of 61% and 20%, respectively are the most infected organs, 53% of patients had one cyst in the bodies and the number of cysts in 8% of cases was more than 3 cysts. Altogether, 41% of CE cases were treated by surgery, 11% with chemotherapy and 48 % with mixed surgery and chemotherapy. Conclusion: Human CE is a major health problem in Iran and it is necessary to establish basic control programs. It is crucial to setting up standard diagnostic methods for early diagnosis, effective treatment, plan educational schedule for different social levels and control the disease in both definitive and intermediate hosts.